2010
DOI: 10.1097/jto.0b013e3181f13682
|View full text |Cite
|
Sign up to set email alerts
|

Standard Outcome Measures for Thymic Malignancies

Abstract: Thymic malignancies present particular issues due to the pace of disease progression, patterns of recurrence, and causes of death that make nuances of how outcomes are reported particularly important. The relatively limited number of patients also creates a challenge to glean as much as possible from the available experience, but risks over-interpretation and potentially misleading conclusions. Therefore the International Thymic Malignancy Interest Group has developed a set of standards for reporting of outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
162
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(165 citation statements)
references
References 31 publications
2
162
0
1
Order By: Relevance
“…We adopted the definition of recurrence recommended by the International Thymic Malignancy Interest Group (Table 1) [11]. Duration of survival or time to recurrence was calculated from the date of operation to the date of event or the last follow-up date.…”
Section: Methodsmentioning
confidence: 99%
“…We adopted the definition of recurrence recommended by the International Thymic Malignancy Interest Group (Table 1) [11]. Duration of survival or time to recurrence was calculated from the date of operation to the date of event or the last follow-up date.…”
Section: Methodsmentioning
confidence: 99%
“…Not surprisingly, the authors found that clinical staging based on CT features could be used to discriminate between stages and was prognostic for survival and progressionfree survival. The CT images included in their study are particularly helpful in illustrating the relevant CT features of the different stages, and their paper adds to the small but growing literature on radiographic assessment of TETs: Marom and colleagues [2] have demonstrated that radiographic features can accurately predict advanced Masaoka stage, and Hayes and colleagues [3] have demonstrated that resectability can likewise be predicted using radiographic features. While it is reassuring that staging of TETs using CT features is prognostic, the value of clinical staging ultimately depends on how closely it correlates with the actual pathologic stage.…”
Section: Invited Commentarymentioning
confidence: 95%
“…hence, such a simple prognostic definition or policy (freedom from recurrence or time to progression) suggested by ITMIG could not be adopted [3]. Therefore, in our study, we used the term progression-free survival (PFS) for all patients as the combined definition for freedom from recurrence and time to progression.…”
Section: Prognosis Evaluationmentioning
confidence: 98%
See 1 more Smart Citation
“…The Masaoka-Koga staging systems [13] were adopted and pathologic results were classified according to WHO histological classification [14]. Recurrent thymoma and recurrence patterns were identified based on the International Thymic Malignancy Interest Group (ITMIG) definitions [15]. One oncologist and two radiologists diagnosed patients with recurrence according to clinical symptoms and the results of CT scan and MRI when needed.…”
Section: Methodsmentioning
confidence: 99%